Chemistry : AS level and A level - "Ratcliff , Brian"; Nicholson, John (Cambridge University Press: Cambridge, 2004)
Chemistry: AS Level and A Level clearly separates AS and A Level material, making this book suitable for both courses. Activities such as chapter learning objectives, questions through the text and end-of-chapter exercises encourage independent learning. The material is suitable for all students, including those for whom English is a second language.
Keywords: Chemistry - Resource book